THE USE OF SPECIFIC AND NON-SPECIFIC QUESTIONNAIRES TO ASSESS QUALITY OF LIFE IN PATIENTS WITH FUNCTIONAL DISORDERS OF INTESTINE - A. E. Shklyaev; Y. V. Gorbunov (SINAPS LLC, 2016)
Objective: comparative assessment of the quality of life of IBS patients in the treatment process with the use of specific and non-specific questionnaires.Materials and methods: a dynamic study of quality of life in 40 patients of IBS with the use of questionnaires GSRS and SF-36.Results: marked decrease in the severity of syndromes on all 6 scales of the questionnaire GSRS, and after 1 to 3 weeks of treatment dynamics was gained statistically significant, and total score improved significantly already after 1 week of therapy. Positive dynamics was obtained on the two scales of the questionnaire SF-36 (social functioning, and emotional functioning), as well as physical and psychological components of health.Conclusions: the high sensitivity of specific questionnaire GSRS and diagnostic significance of nonspecific SF-36 questionnaire in patients with IBS, the necessity to combine them.